The structure of dynamic and kinematic limb motion in a taekwon-Do European champion during turning kicks. - Wasik, J.; Gora, T.; Michalski, C. (Journal of Kinesiology and Exercise Sciences, 2014)
Aim. The aim of this study was to identify the dynamic and kinematic factors influencing the movement of turning kicks on the basis of the obtained limb speed values, pressure on the ground and kick time. Material and methods. The subject of our study was a 17-year-old athlete, weighing 75 kg, 179 cm tall, holder of the 1st Dan degree, winner of the European ITF Taekwon-Do championship. The study used the Italian BTS Spa Smart-D system for complex motion analysis. Results. Indicators describing the structure of space-time movement markers placed on the foot and wrists of both arms were registered, thus defining their speed change as a function of time. The mean values of the parameters were used to determine the curve of velocity changes as a function of the relative length (performing kick) of the competitor`s lower limb. The mean maximum speed of the foot and arms was determined in this manner in regard to X, Y and Z axes, respectively, and also the kick time, maximum pressure of the supporting foot on the ground as well as the pressure force of the kicking foot during its take-off. Conclusions. Kicking foot speed correlates with the sweeping movement of the arms (r = 0.64 for the right arm and r = 0.61 for the left). This may indicate that kinetics of the turning kick may depend on the correctness and dynamics of the arm sweep. The measurement results of the pressure force of the supporting foot on the ground show three characteristic peaks. The first is evident shortly after foot take-off and strongly correlates with the speed of the kicking foot (r=0.91). The second appears at the time of obtaining maximum speed of the other foot and the third informs about returning to initial stance.